How to DeFi : Advanced - Fang, Lucius, ....-; Hor, Benjamin, ....-; Azmi, Erina, ....-; Win Win, Khor, ....- (S.l. : CoinGecko, 2021)
Decentralized Finance's (DeFi) mission is clear: reinventing traditional finance's infrastructure and interface with greater transparency, accessibility, efficiency, convenience, and interoperability. By April 2021, there has been over $86 billion worth of cryptocurrencies locked up in the DeFi applications, 86 times larger than a year ago. The traditional financial industry is getting rapidly disrupted and DeFi is reshaping the way global financial systems operate. In this book, you will learn about various decentralized financial primitives, such as stablecoins, exchanges, lending, insurance, derivatives, and more. DeFi has already existed since 2018, but it has recently witnessed a surge in popularity in the first half of 2021 with no ceiling in sight. Use this book to gain insight into the novel financial innovations enabled by DeFi. Join us in this exciting adventure of redefining finance. In this book, you will discover: What is DeFi and the key categories within it An insider's look at how to evaluate various DeFi protocols Services that empower the DeFi ecosystem: Oracles and Data Aggregators Multichain bridges that seamlessly connect and move funds between blockchains Causes of DeFi exploits and how can you avoid them.